A Study Of Internet Protocol Digital Microwave Radio (IP DMR) Propagation Delay Affected Downtime In Oil And Gas Company - Samsudin, Nooraida; Ahmad, Azham (International Journal of Advanced Science Computing and Engineering, 2019)
Â Internet Protocol Digital Microwave Radio (IP DMR) is a significant impact on the trunk mobile communication between platform. Thus, the goal of downtime is a crucial problem especially in oil and gas company. Based on the examines from the previous issues such as relative costing based on previous hardware requirements and possible implementation, and upgrade that contribute to the long term communication flexibly on all radio in the platform system. This paper will examine the downtime that affect the network by calculate the propagation delay using SLA given and compare the SLA for Digital Microwave Radio (DMR) and Internet Protocol Digital Microwave Radio (IP DMR) that contribute to the process